Filantropi Islam dan Kristen: Studi Komparatif - Muh Luqman Arifin; Rofiq Nurhadi; Ida Zahara Adibah (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
Poverty after the covid-19 pandemic has increased significantly. Without proper handlers it will have an impact on the distability of security and social life. Religion as a source of teachings and morals has a responsibility in providing solutions to this problem. The purpose of this study was to find this form of responsibility within Islam and Christianity. The two religions have the largest adherents in Indonesia. Knowing the role that is owned determines the spectrum of life in Indonesia. This research uses a type of qualitative research with a normative- sociological approach by taking data on the texts of the Qur'an and the Gospels that talk about philanthropy and understand the verses as religious believers, then see how the verses and texts are implemented in people's lives by both religious believers. The results showed that first, the two religious teachings have a theological basis to alleviate poverty. Second, both have distinctive terms in the form of material assistance, in Islam it is known as zakat, infak, almsgiving, and waqf, while in Christianity it is called collective, karitas, donations. The conclusion of this study is that Islam and Kristin both have a theological foundation that can be used as a basis for alleviating poverty so that their adherents can not only play their own roles, but can cooperate with each other.